Shear bond strength between porcelain and nano filler composite resin with or without 9% hydrofluoric acid etching - Kun Ismiyatin (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Reparation technique on restorations with broken or damaged porcelain which are still attached with the teeth are difficult, because it is very hard to remove the porcelain restoration without damaging it, and it needs a long time. Various ways have been developed to repair the broken porcelain, one of them is the use of composite resin as the material for the restoration of fractured porcelain. Repairing porcelain inside the mouth without removing the restoration of the damaged porcelain using light cured composite resins material seems to be an advantageous option because it is relatively simple, has low risks, good esthetically and cheap. Purpose: The objective of this study was to find out the difference of shear bond strength in porcelain reparation using nano filler composite resin with or without 9% hydrofluoric acid etching by using Autograph measuring device. Methods: Twenty pieces of the porcelain samples devided into 2 groups. Group I: etching process using 9% hydrofluoric acid, and group II : without etching process. Result: The data was analyzed using t test in a p value of 0.0001 (p≤0.05), which means there is a significant different of shear bond strength between treated group I and II. The biggest shear bond strength was in treatment group I. Conclusion: The use of 9% hydrofluoric acid on the surface of porcelain can increase the shear bond strength between porcelain and nano filler composite resin.